2019
DOI: 10.1136/bmjopen-2018-026994
|View full text |Cite
|
Sign up to set email alerts
|

Within-individual analysis of pain and sickness absence among employees from low and high occupational classes: a record linkage study

Abstract: ObjectivesPain is linked to an increased risk of sickness absence (SA); however, the extent to which unmeasured time-invariant differences explain this association is yet unknown. Therefore, we determined the within-individual associations between pain and short-term (in the survey year) and long-term (2 years following the survey years) SA risk in high and low occupational classes while controlling for the potential bias due to unobservable time-invariant characteristics.MethodsThe Helsinki Health Study data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Physical and psychosocial strain at work have been linked to both pain and SA [ 47 49 ]. Occupational class differences in the association between pain and SA have been documented, and work-related factors likely contribute to the causal pathway between pain, mental health, and SA [ 50 ]. To avoid overadjustment bias, we did not adjust the analyses for work-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Physical and psychosocial strain at work have been linked to both pain and SA [ 47 49 ]. Occupational class differences in the association between pain and SA have been documented, and work-related factors likely contribute to the causal pathway between pain, mental health, and SA [ 50 ]. To avoid overadjustment bias, we did not adjust the analyses for work-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that conditional fixed effects do not truly control for the fixed covariates when used with negative binomial regression models (25). To overcome the limitations of both models, an alternative solution, a so-called hybrid model, was selected as proposed by Allison (26) in the spirit of Mundlak (27) and previously used elsewhere (28)(29)(30). In the hybrid model, a random effects model is fitted with two variables for each time-varying regressor: individualspecific mean value and individual-specific variance to control for the between-and within-individual effects, respectively.…”
Section: Within-individual Associationmentioning
confidence: 99%
“…Chronic pain is common among employees and in work life. It is associated with problems such as reduced work capacity [ 1 ] and sickness absence [ 2 ]. There is increasing evidence that childhood adversities contribute to various adult health outcomes [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%